2019
DOI: 10.1590/1679-78254665
|View full text |Cite
|
Sign up to set email alerts
|

New hybrid approach for free vibration and stability analyses of axially functionally graded Euler-Bernoulli beams with variable cross-section resting on uniform Winkler-Pasternak foundation

Abstract: In this paper, a new hybrid approach is presented based on the combination of the power series expansions and the Rayleigh-Ritz method for stability and free vibration analyses of axially functionally graded non-uniform beams resting on constant Winkler-Pasternak elastic foundation. In the proposed novel technique, the power series approximation is first adopted to solve the motion equation. Regarding this numerical methodology, the transverse displacement and all mechanical properties are expanded in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…The results are compared with the ones given by Ref. [21]. Effect of the power law index parameter, α on the Modulus of Elasticity, E, of the beam is demonstrated in Figure 9.…”
Section: Euler-bernoulli Beam Resultsmentioning
confidence: 94%
“…The results are compared with the ones given by Ref. [21]. Effect of the power law index parameter, α on the Modulus of Elasticity, E, of the beam is demonstrated in Figure 9.…”
Section: Euler-bernoulli Beam Resultsmentioning
confidence: 94%
“…Owing to its strength, stiffness, and lightweight nature, it finds widespread use in aerospace, automotive, marine, and defense engineering fields [2]. Functional gradient beams (FGBs), as the most fundamental structural element in aerospace, mechanical, and civil engineering, address the issue of delamination and stress concentration inherent in composite materials [4]. Various scholars use methods such as the differential quantization method (DQM) and generalized differential quantization method (GDQM) to investigate FGBs along different gradient directions.…”
Section: Introductionmentioning
confidence: 99%
“…Rajasekaran and Khaniki examined the vibration characteristics of nanobeams with bidirectional functional gradient variable sections on elastic foundations, utilizing the explicit and implicit finite element methods and the Wilsontheta method [20]. Hareram et al investigated the impact of different material grading parameters on the mechanical properties of axial FGBs on elastic foundations using the differential product method [9] (Soltani and Asgarian, 2019). By employing the differential transformation method, Shahba and Rajasekaran introduced the differential transformation element method to solve the displacement curve of a tapered beam with variable-section axia l functional gradient, significantly enhancing calculation convergence speed [15].…”
Section: Introductionmentioning
confidence: 99%
“…The model of beams resting on elastic foundation have a wide range of applications in civil engineering, such as underground pipelines, rails, strip foundations, pile foundations, etc. [1][2][3][4][5] Winkler elastic foundation is treated as a single-parameter model and commonly used by engineers and researchers, but this model ignores the shearing interaction between soil elements. Previous studies have shown that [6,7], the assumption always results in a huge deviation.…”
Section: Introductionmentioning
confidence: 99%